2013
DOI: 10.1038/hdy.2013.103
|View full text |Cite
|
Sign up to set email alerts
|

Landscape features and helminth co-infection shape bank vole immunoheterogeneity, with consequences for Puumala virus epidemiology

Abstract: Heterogeneity in environmental conditions helps to maintain genetic and phenotypic diversity in ecosystems. As such, it may explain why the capacity of animals to mount immune responses is highly variable. The quality of habitat patches, in terms of resources, parasitism, predation and habitat fragmentation may, for example, trigger trade-offs ultimately affecting the investment of individuals in various immunological pathways. We described spatial immunoheterogeneity in bank vole populations with respect to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 78 publications
3
48
3
Order By: Relevance
“…; Guivier et al . ). Extensive convergence in immune gene expression, shown here, highlights the magnitude and importance of environmental effects on host immunity in nature, which are relatively stronger than the fixed between‐population differences, for most genes examined here.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Guivier et al . ). Extensive convergence in immune gene expression, shown here, highlights the magnitude and importance of environmental effects on host immunity in nature, which are relatively stronger than the fixed between‐population differences, for most genes examined here.…”
Section: Discussionmentioning
confidence: 97%
“…; Guivier et al . ), contributing to positive selection on host genes (Duffy & Sivars‐Becker ), genetic polymorphisms (Yasukochi & Satta ), local adaptation (Eizaguirre et al . ), population divergence (Scharsack et al .…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated variability at eight single nucleotide polymorphisms that have been previously identified in M. glareolus from Fennoscandia (see for details Supporting Information Table ; Guivier et al, ; Dubois, Galan, et al, ). Note that we focused on a single SNP within Tnf promoter as it had previously been shown to be involved in PUUV/ M. glareolus interaction (Guivier et al, ). We used KASP genotyping services from LGC company (Genotyping by Allele‐Specific Amplification; Cuppen, ) to genotype all sampled voles at these SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…Additional studies of bank vole populations aimed at characterizing spatial differences in SNP allele frequencies or gene expression levels in candidate genes presumably repressing PUUV replication. These studies reported that tumor necrosis factor (Tnf) promoter polymorphisms and variations in Mx2 gene expression correlated with PUUV distribution in bank vole populations and NE epidemiology (Dubois, Galan, et al, 2017;Guivier et al., 2010;Guivier, Galan, Henttonen, Cosson, & Charbonnel, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This information content is attested to by the increasing use of transcriptomic approaches in modern biology. More specifically, early indications in wild rodents suggest that gene expression measurements, especially if interpreted with the complexity of post‐transcriptional dynamics in mind, do contain much useful information.…”
Section: What Study Systems and Measurements To Use?mentioning
confidence: 99%